1998
DOI: 10.1074/jbc.273.10.5869
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-sensitive Mutations of the CKA1 Gene Reveal a Role for Casein Kinase II in Maintenance of Cell Polarity in Saccharomyces cerevisiae

Abstract: Casein kinase II (CKII) of Saccharomyces cerevisiae contains two distinct catalytic subunits, ␣ and ␣, that are encoded by the CKA1 and -2 genes, respectively. We have constructed conditional alleles of the CKA1 gene. In contrast to cka1 cka2 ts strains, which exhibit a defect in both G 1 and G 2 /M cell cycle progression, cka1 ts cka2 strains continue to divide for three cell cycles after a shift to restrictive temperature and then arrest as a mixture of budded and unbudded cells with a spherical morphology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 44 publications
2
58
0
Order By: Relevance
“…The activity was normalized to CDC25B3 quantity detected in Western-blot and expressed as a fold activation compared to CDC25B3 activity detected in the simple infection. These results are representative of four independent experiments CK2 regulates CDC25B phosphatase activity N Theis-Febvre et al M phases (Mulner-Lorillon et al, 1988;Padmanabha et al, 1990;Hanna et al, 1995;Rethinaswamy et al, 1998). In this study, we have shown that, in vitro, CK2 kinase phosphorylates specifically one of the two CDC25 phosphatases implicated in the regulation of the G2/M transition.…”
Section: Discussionmentioning
confidence: 58%
“…The activity was normalized to CDC25B3 quantity detected in Western-blot and expressed as a fold activation compared to CDC25B3 activity detected in the simple infection. These results are representative of four independent experiments CK2 regulates CDC25B phosphatase activity N Theis-Febvre et al M phases (Mulner-Lorillon et al, 1988;Padmanabha et al, 1990;Hanna et al, 1995;Rethinaswamy et al, 1998). In this study, we have shown that, in vitro, CK2 kinase phosphorylates specifically one of the two CDC25 phosphatases implicated in the regulation of the G2/M transition.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, likely physiological targets for CK2 include a number of proteins that regulate intracellular trafficking such as p65 (synaptotagmin) (72), furin (73,74), and dynein (75). The observations that CK2␣ is implicated in the polarized growth of both fission and budding yeast cells (76,77), as well as neuritogenesis in mouse neuroblastoma (N2A) cells (78), also suggests a role for CK2 in the organization of the actin cytoskeleton. In fact, many proteins that interact with the cytoskeletal regulating GTPases (Rac, Rho, and cdc42) possess PH domains, leucine zippers, prolinerich regions, and/or kinase domains (79).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several microtubule-associated proteins (MAPs) seem to be involved in interconnecting microtubules to each other, as well as to the plasma membrane (Gull 1999). Previous reports have suggested that CK2 plays an important role in the maintenance of cell morphology and polarity (Ulloa et al 1994, Rethinaswamy et al 1998. Also, coimmunoprecipitation and in vitro binding studies have evidenced that CK2 is strongly associated to tubulin in mammalian cell extracts (Faust et al 1999).…”
Section: Discussionmentioning
confidence: 99%